300 TAHUN LINNAEUS: PANDANACEAE, LINNAEUS DAN KONEKSI SWEDIA - Keim, Ary Prihardhyanto (BERITA BIOLOGI, 2007)
Pandanaceae is one of the three large and important families within the Monocotyledoneaie consisting of approximately 900 species found only in the Old World Tropics. Malesia is the region of importance for the fanmyfwhere the prominent diversity and the three principal genera (Freycinetia, Pandanus, and Sararanga) are found.Pandanaceae is also an important family of the Monocotyledoneae in the Malayo-Austronesian and^elanesian cultures.The usage of pannans in the Melanesian culture is more diverse and incorporating more number of species. Although pandan was first described by the two distinguish Dutch naturalists, Rumphius and Rheede tot Drakenstein, the introduction of pandan into the world of Botany was started and in the early stage also involved Swedish botanists, from Linnaeus to Fagerlind. Linnaeus still suggested Pandanus as a possibly member of Bromelliaceae. Linnaeus Jr. placed it as a genus of its own, Pandanus, thus laid the firm foundation for the classification of the genus and the entire family.The information on Pandanaceae encompassing morphology to history is described in this paper, including the significance of the family in relation with the Agenda 21.